1983
DOI: 10.1128/aac.23.6.918
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal beta-lactamases of Enterobacter cloacae are responsible for resistance to third-generation cephalosporins

Abstract: About 70%o of all Enterobacter cloacae strains tested possessed one of two species-specific 3-lactamases. These enzymes, E. cloacae ,B-lactamase A and E. cloacae ,-lactamase B, with isoelectric points of 8.8 and 7.8, respectively, had the same pH and temperature optima. Both showed similar enzyme kinetics and were inhibited by cloxacillin but not by p-chloromercuribenzoate. E. cloacae 3-lactamase B appeared to be identical with the enzyme of E. cloacae P99. By a mutation in a regulatory gene, inducible enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 25 publications
1
85
0
Order By: Relevance
“…In particular, thepI 8.4 enzyme exhibited moderate k,,, (40/min) and K , (40 p~) values for cefotaxime, whereas k,,, and K , of this drug for P99 enzyme are about l/min and 1 PM respectively (Bush et al, 1982;Livermore et al, 1986). The PI 8.4 enzyme also differed from the E-2 form of Ia enzyme described by Seeberg et al (1983) and Bush et al (1985), both in its kinetics of activity against cefotaxime, wherein E-2 resembled P99 enzyme, and in the stability of its imipenem complex. Bush et al (1985) reported a half-life of only 0.8 min for the E-2 enzyme-imipenem complex ; considerably less than that observed here for the PI 8.4 enzyme.…”
Section: Discussionmentioning
confidence: 84%
“…In particular, thepI 8.4 enzyme exhibited moderate k,,, (40/min) and K , (40 p~) values for cefotaxime, whereas k,,, and K , of this drug for P99 enzyme are about l/min and 1 PM respectively (Bush et al, 1982;Livermore et al, 1986). The PI 8.4 enzyme also differed from the E-2 form of Ia enzyme described by Seeberg et al (1983) and Bush et al (1985), both in its kinetics of activity against cefotaxime, wherein E-2 resembled P99 enzyme, and in the stability of its imipenem complex. Bush et al (1985) reported a half-life of only 0.8 min for the E-2 enzyme-imipenem complex ; considerably less than that observed here for the PI 8.4 enzyme.…”
Section: Discussionmentioning
confidence: 84%
“…The resistance of these bacteria is principally due to constitutive overexpression of chromosomal ampC (which encodes AmpC, a class C ␤-lactamase) (5,33). The ampC gene is located on the chromosome of many gram-negative bacilli and is inducible in the presence of ␤-lactam antibiotics (9).…”
mentioning
confidence: 99%
“…MICs were not (or only by one dilution) elevated against Citrobacter and Enterobacter strains, highly resistant to third-generation cephalosporins. This behaviour reflects the extreme stability of the drug to /Mactamases, since it has been shown that cephalosporin resistance in such strains is due to chromosomal cephalosporinase (Sanders & Sanders 1983, Seeberg et al, 1983. Sch 34343, thus, together with imipenem, can be considered as potent chemotherapeutic agents in infections caused by Enterobacteriaceae resistant to third-generation cephalosporins and to aztreonam.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that Enterobacteriaceae can become resistant to thirdgeneration cephalosporins by mutation in a chromosomal locus, regulating the production of a cephalosporinase (Seeberg, Tolxdorff-Neutzling & Wiedemann, 1983). The frequency of resistant mutants of this type in clinical isolates is still low (Kayser & Kohler, 1984).…”
Section: Comparison Of Sch 34343 With Other Fi-lactam Antibiotics Agamentioning
confidence: 99%